2003
DOI: 10.4049/jimmunol.170.7.3883
|View full text |Cite
|
Sign up to set email alerts
|

Complement Factor C5a Mediates Renal Ischemia-Reperfusion Injury Independent from Neutrophils

Abstract: The complement system has been shown to mediate renal ischemia-reperfusion (I/R) injury. However, the contribution of complement factor C5a to I/R injury, in particular in the kidney, remains to be established. In this study, we investigated the impact of blocking the C5aR pathway on the inflammatory response and on the renal function in a murine model of I/R injury. First, we analyzed C5aR expression in kidneys of healthy mice. Intriguingly, we found expression on mesangial, as well as on tubular epithelial, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
169
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 217 publications
(178 citation statements)
references
References 41 publications
(48 reference statements)
6
169
3
Order By: Relevance
“…In a previous study, de Vries et al (6) showed that C5a-mediated renal IRI in the mouse was independent of neutrophils. In this regard, it is of interest to note a dissociation between renal IRI and neutrophil infiltration in CVFtreated CD55 Ϫ/Ϫ CD59 Ϫ/Ϫ mice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a previous study, de Vries et al (6) showed that C5a-mediated renal IRI in the mouse was independent of neutrophils. In this regard, it is of interest to note a dissociation between renal IRI and neutrophil infiltration in CVFtreated CD55 Ϫ/Ϫ CD59 Ϫ/Ϫ mice.…”
Section: Discussionmentioning
confidence: 99%
“…Both anaphylatoxin-and MAC-mediated tubular injuries have been proposed as potential mechanisms for complement-dependent pathogenesis of renal IRI (6,8,9). Although we demonstrated that exacerbated renal IRI in CD55 Ϫ/Ϫ CD59 Ϫ/Ϫ mice was complement dependent, the mediator(s) responsible for the increased renal injury remains to be defined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All of these compounds are potent CD88 antagonists in vitro; however, only the C5a mutants C5aRAM (24) and jun/fos-A8 (25), the cyclic peptide AcPhe[L-ornithinePro-D-cyclohexylalanine-Trp-Arg] (AcF-(OpdChaWR)) (29), and a nonpeptidic antagonist (23) have been proven useful in vivo. Administration of these inhibitors protects animals from in-flammatory responses in immune complex disease (25,29,30), ischemia/reperfusion injury (25,31,32), and C5a-induced neutropenia (23,24). The molecular mechanisms underlying the C5aR antagonism are largely unknown.…”
mentioning
confidence: 99%